Active recall to increase HIV and STI testing: a systematic review. (10th March 2015) - Desai, Monica; Woodhall, Sarah C; Nardone, Anthony; Burns, Fiona; Mercey, Danielle; Gilson, Richard
Abstract : Background: Active recall can improve reattendance rates and could increase retesting rates and detection of HIV and sexually transmitted infections (STIs), but the best strategy remains uncertain. Methods: We conducted a systematic review and meta-analysis of active recall for HIV and/or STI testing. We searched six electronic databases using terms for HIV, STIs, tests and active recall (defined as a reminder to retest for HIV/STIs) for randomised, non-randomised and observational English-language studies published between 1983 and 2013. Outcomes included reattendance/retesting rate and STI diagnosis at follow-up. Results: Of 5634 papers identified, 17 met the inclusion criteria. Of the 14 comparative studies, all but one demonstrated higher reattendance/retesting rates in the intervention group, but the range was wide (17.5–89%). Meta-analysis of nine RCTs found reattendance/retesting rates were significantly higher in the intervention versus control groups (pooled OR 2.42 (95% CI 1.84 to 3.19)). In a subgroup analysis, home sampling increased retesting compared with clinic testing (pooled OR 2.20 (95% CI 1.65 to 2.94)). In observational studies SMS reminders increased retesting compared with standard clinic care (pooled OR 2.19 (95% CI 1.46 to 3.29)), but study estimates were highly heterogeneous (I 2 =94%, p<0.001). Conclusions: Active recall interventions are associated with higher reattendance/retesting rates for HIV/STI. Although home sampling and SMS reminders were associated with higher reattendance/retesting rates in most studies, evidence is limited by the heterogeneity of interventions and control groups and the quality of studies. Further work is needed to explore which active recall modality is clinically cost-effective and acceptable for HIV/STI screening.